Effect of classical surgical treatment under spinal anesthesia on venous thromboembolism in varicose veins patients - Doğukan, Mevlüt; Kaplan, Esma (Journal of Surgery and Medicine, 2020)
Aim: Although minimally invasive methods have developed rapidly in the treatment of varicose veins in recent years, high ligation + stripping (S/L), which is the classical surgical treatment, is still considered gold standard. Some thromboembolic events may occur due to varicose disease. Our aim is to determine the changes in mean platelet parameters after the procedure in patients who underwent S/L with spinal anesthesia and investigate the effect of this procedure on thromboembolic events. Methods: Patients who visited the Anesthesia Reanimation outpatient clinic of Adiyaman University Faculty of Medicine and underwent S/L with spinal anesthesia were evaluated in this retrospective cohort study. Data was collected electronically with file scanning. Patients whose hemograms were obtained before and 1 day after the operation were included. Among the laboratory tests, MPV, PLT, platelet distribution width (PDW) and plateletcrit (PCT) were noted. Results: Postoperative MPV (P<0,001) and PLT (P=0.01) values showed a significant decrease compared to the preoperative period, while PDW (P=0.194) and PCT (P=0.863) values remained similar. Conclusion: If it is assumed that varicose veins and MPV are associated with thromboembolic events, a significant decrease in postoperative MPV value in patients who underwent S / L with spinal anesthesia will reduce thromboembolic events.